Solid Dispersion of Acetosal Using Polyvinyl Pyrrolidone (PVP) K-30 in Tablets with Direct Compressing Method - Khasanah, Khuswatun; Nawangsari, Desy; Kusuma, Ikhwan Yuda (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Acetosal is classified in the Biopharmaceutical Classification System (BCS) class II (low solubility, high permeability). Low solubility causes a decreased dissolution rate. Polyvinyl pyrrolidone (PVP) K-30 is an inert carrier easily soluble in water and can influence the solubility of a drug substance. Efforts to increase the solubility of acetosal make a solid dispersion system. This study aims to determine the effect of the solid dispersion system of acetosal: PVP K-30 on dissolution rate, the ratio of the solid dispersion with the best dissolution rate, and the physical properties of acetosal tablets formed in the dispersion system. Solid dispersions using the dissolving method with variations in the concentration of acetosal: PVP K-30 1:1, 1:3, and 1:5. The results of the dissolution test of acetosal in solid dispersion powder, i.e., PVP Formula 1:5, which has the highest dissolution percentage compared to formula 1:1 and 1:3 with the concentration this formula was 140.96 mg, dissolution percentage was 28.19±0,63% in 30 minutes. Statistical results by ANOVA test show a significant difference of 0.044 (p<0.05). The physical properties of tablets with a dispersion system show higher addition of PVP K-30. This result is related to slower disintegration time and lower friability.